The nursing strategies for preventing post-percutaneous coronary intervention hematomas: a review - Kaur, Gagandeep; Singh, Rajdevinder (International Journal Of Community Medicine And Public Health, 2024)
Post-percutaneous coronary intervention (PCI) hematomas pose significant risks for patients and can lead to severe morbidity and mortality if left unaddressed. Nurses play a vital role in preventing these complications, emphasizing the importance of their understanding and implementation of nursing strategies and interventions. This comprehensive review investigates the various nursing strategies and interventions aimed at mitigating the risk of post-PCI hematomas and improving patient outcomes. A systematic search across multiple medical databases and scholarly sources yielded data on preventive measures and treatment options for post-PCI hematomas. The review underscores the significance of nursing interventions, including patient education, pressure dressings, careful hemostasis, and medication management, in reducing the occurrence of hematomas. It also highlights the potential complications associated with post-PCI hematomas, emphasizing the necessity of timely intervention and patient education to minimize the risk. The review emphasizes the critical role of nurses in the prevention and management of post-PCI hematomas and provides insights for future research and quality improvement initiatives. Overall, the review serves as a valuable resource for healthcare professionals, offering a comprehensive understanding of nursing interventions and guidelines to enhance patient safety and minimize the incidence of post-PCI hematomas.